Metformin and insulin treatment prevent placental telomere attrition in boys exposed to maternal diabetes - Garcia-Martin, Isabel (PLoS One, 2018)
Shortened leukocyte and placental telomeres associated with gestational diabetes mellitus (GDM) suggest this exposure triggers telomere attrition contributing to adverse outcomes. We applied high resolution Single Telomere Length Analysis (STELA) to placenta from GDM pregnancies with different treatment pathways to determine their effectiveness at preventing telomere attrition. Differences in telomere length between control (N = 69), GDM lifestyle intervention (n = 14) and GDM treated with metformin and/or insulin (n = 17) was tested by Analysis of Covariance (ANCOVA) followed by group comparisons using Fisher’s least significant difference. For male placenta only, there were differences in mean telomere length (F(2,54) = 4.98, P = 0.01) and percentage of telomeres under 5 kb (F(2,54) = 4.65, P = 0.01). Telomeres were shorter in the GDM lifestyle intervention group compared to both controls (P = 0.02) and medically treated pregnancies (P = 0.003). There were more telomeres under 5 kb in the GDM lifestyle intervention group compared to the other two groups (P = 0.03 and P = 0.004). Although further work is necessary, we suggest that early adoption of targeted medical treatment of GDM pregnancies where the fetus is known to be male may be an effective strategy for ameliorating adverse outcomes for children.